Chapter 5. Work Through the Valley: Do - Jones, Loretta (Ethn Dis, 2009)
Much of the work for a community-partnered participatory research (CPPR) initiative is done in committees that operate under the principles of CPPR and the vision of the partnership, while implementing the action plans of the initiative. Action plans are developed in work group meetings and sponsored events that engage the community in discussion about programs or new policy directions. This article provides detailed recommendations for conducting meetings, completing assignments, and running events as the main body of work.